Cultural and creative actors in non-urban areas: enacting local stewardship as a regenerative approach - Duxbury, Nancy; Silva, Sílvia; Hildibrandsdóttir, Anna Hildur (Frontiers in Communication, 2026)
Cultural and creative actors in non-urban areas contribute to local regenerative actions through practices of stewardship and place-based creativity. This article focuses on how a key principle of regenerative development, “stewardship of the resources of place, identity, and unique potential,” is conceived and enacted. The study aims to deepen understanding of how regenerative forms of local development that nurture social, cultural, and ecological vitality can emerge from grassroots initiatives. Drawing on 12 case studies from six European countries within the Horizon Europe IN SITU project, the analysis employs a comparative qualitative approach informed by reflexive monitoring reports. Research findings confirm that cultural and creative actors operationalize regenerative micro-processes by engaging simultaneously in heritage stewardship, encouraging place-inspired creative work, building the capacity of locally-based creators, reinforcing connections to place through a local socioeconomic focus, and using and improving public space. The analysis reveals a dynamic understanding of heritage as a living resource that is actively re-contextualized to drive new social and economic aspirations. Furthermore, creative processes and outputs are anchored in local identity yet generate transferable knowledge and methodologies. The actors’ intentions and dedication to creatively address key local issues through their projects demonstrates the potential of cultural and creative actors to contribute as drivers of local change and transition in meaningful ways. This potential is challenged, however, by precarious situations in which the pragmatic sustainability of livelihoods and the fragility of initiatives are common concerns.